2011
DOI: 10.3171/2010.9.spine10151
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ICD-9–based, retrospective, and prospective assessments of perioperative complications: assessment of accuracy in reporting

Abstract: Object Large studies of ICD-9–based complication and hospital-acquired condition (HAC) chart reviews have not been validated through a comparison with prospective assessments of perioperative adverse event occurrence. Retrospective chart review, while generally assumed to underreport complication occurrence, has not been subjected to prospective study. It is unclear whether ICD-9–based population studies are more accurate than retrospective reviews or are perhaps equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
76
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(77 citation statements)
references
References 36 publications
1
76
0
Order By: Relevance
“…Complications and their association with an operative approach, surgical indication, and other comor- bidities have been reported in separate manuscripts. [4][5][6]27,28 However, the rate of overall complications is higher in the present series than many others that retrospectively evaluated perioperative complications after spinal fusion. The prospective design of our investigation relied less on the medical record and recall of the investigators and more on the accumulation of essential clinical details prospectively throughout the patient's hospital course; a recent review confirmed that prospective studies identified a statistically higher incidence of complications.…”
Section: Discussionmentioning
confidence: 40%
“…Complications and their association with an operative approach, surgical indication, and other comor- bidities have been reported in separate manuscripts. [4][5][6]27,28 However, the rate of overall complications is higher in the present series than many others that retrospectively evaluated perioperative complications after spinal fusion. The prospective design of our investigation relied less on the medical record and recall of the investigators and more on the accumulation of essential clinical details prospectively throughout the patient's hospital course; a recent review confirmed that prospective studies identified a statistically higher incidence of complications.…”
Section: Discussionmentioning
confidence: 40%
“…In both studies, substantial proportions of forms were not completed by the time of patient discharge, requiring the forms to be returned to the attending surgeons to be completed retrospectively. This weakens the quality of adverse-event reporting as the underlying premise is that the data collected prospectively are superior to retrospective data [6,8,42]. Our data showed similar complication rates among prospectively and retrospectively collected data.…”
Section: Discussionsupporting
confidence: 56%
“…11,12 In turn, the use of such databases for research purposes also presents some potential limitations relating to the accuracy and validity of the coding of diagnoses. [13][14][15] Other limitations of this study include the fact that, although hospital level of care and hospital volume were known for each delivery year, data on hospital services were only available for the year 2001 and were extrapolated to the other years in which individual-level data were available. Future studies should therefore focus on the more precise evaluation of these hospital services, as their presence or absence may vary over time, in addition to other potential hospital characteristics that may affect neonatal outcomes, such as the 24-h availability of obstetrical anesthesia services and in-house obstetrical services.…”
Section: Discussionmentioning
confidence: 99%